The effect of indoor air quality on health and performance of labors in joinery factories - Sadeghi, Hengameh (2020)
Dubai is one of the most flourishing cities in the region. The lifeblood of the UAE economy is the construction industry, which is the pillar of Dubai’s future progression. There are around 15,000 projects launched in UAE in 2019, based on the BNC construction projects journal, whereas around 65 percentages of projects implemented in Dubai. In addition, the foundation of development has a significant rise since 2013 when EXPO 2020 awarded to Dubai. The expected annual construction growth rate predicted around 4.64 percent from 2019 till 2023 based on Pinsent Masons’ annual GCC construction survey whiles 33.1 percentage of Dubai construction covers residential projects. Accordingly, Dubai UAE population has steadily moved since 2010. The population of people in the UAE is 9.68 million in 2019 whilst Dubai has the largest population by 35.7 percentages based on official UAE Government Status, 2018. The growing population and the rising number of investors have a huge impact on the construction industry, and the demand for joinery items will increase. Wood has been well known for thousands of years as one of the first few natural renewable resources in the world (Rastogi et al. 1989). And still, it has its popularity. It is mostly because wood and wood products are known for minimizing the carbon dioxide in the atmosphere that has a lower carbon footprint. Despite the fact, joinery production produced a considerable amount of wood dust, which are invisible fine particles in the air. In the wood industry, airborne wood dust has the highest prevalent occupational exposure for workers. According to the WHO in most developing countries, 12.2 million workers die because of an unsafe healthy work environment by active working age. The emitted airborne wood dust can lead to an incremented risk of different health problems especially, in the process of sanding, sawing, routing, and cutting. According to the International Agency for Research on Cancer (IARC), wood particles intervention the respiratory system, which decreases the lung capacity and causes signs such as, allergic reaction, irritation of eyes, nose, and throat, and cancer (Sawane & Sawane 2017). According to the health and social care legislation abolished by DHA, the health of the workers is considered important. Considering that, the health of labors plays the most vital prerequisite of their productivity, performance, and great opportunities for businesses, which has a direct influence by the working place environment. This study reveals the importance of the workers’ health in the woodworking industry and perceived the safe & healthy environment as per global IAQ standards. Considering the fact that green technology made a remarkable improvement in real-world performance, the quality of indoor air has the same level of qualification as the healthy building’s structure. The result of this research can have a significant impact on the health of workers, and joinery factories can redesign their facilities accordingly. Also, it can be a lead model for future building if it ignores, the reputation of fatality and injuries of labors increased.